Analysis of the Form and Amount of Compensation in the Copyright Infringement Case for the Use of the Song "Lagi Syantik" by Gen Halilintar Without Permission - Putu Febby Regina Pingkan; I Gede Agus Kurniawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Copyright infringement on digital platforms is increasing with the development of social media as a means of content distribution. One case that has attracted public attention is the use of the song "Lagi Syantik" by the Gen Halilintar family without permission from the rights holder. This article analyzes the form and amount of compensation awarded in this case, and examines the effectiveness of the implementation of Law No. 28 of 2014 in addressing copyright infringement in the digital ecosystem. This research uses a normative juridical method with a case study approach and a comparative study of legal systems in other countries, such as the United States, Japan, and Germany. The results show that the determination of compensation of Rp 300 million does not reflect an objective approach to calculating losses, both economic and immaterial. The judge did not specify the basis for calculating the value of the losses, and the Indonesian legal system does not yet provide a standard or technical institution capable of accurately estimating royalties from digital platforms. International practice demonstrates the importance of the principles of fictitious licensing, statutory damages, and the presumption of damages mechanism as solutions to the difficulties of proving digital losses. Therefore, it is necessary to establish a digital copyright damage evaluation agency, revise the Copyright Law, and integrate the infringement reporting system with digital platforms. These reforms are crucial to ensure justice and legal certainty for creators in the digital creative economy era.